2019
DOI: 10.1049/iet-nde.2019.0013
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and dielectric properties of sub‐micron hollow sphere (Ba 0.6 Sr 0.4 )TiO 3 /PVDF composites

Abstract: Hollow sphere (Ba 0.6 Sr 0.4)TiO 3 (HS-BST) powders with sub-micron size and different shell thickness were synthesised through template-assisted method. HS-BST/poly(vinylidene fluoride) (PVDF) composites were prepared using tape casting method. The effects of particle size and shell thickness of HS-BST on the microstructure, dielectric tunability, and energy storage properties of HS-BST/PVDF composites were investigated. Results showed that all HS-BST particles were uniformly dispersed in PVDF matrix without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The sudden increase in the dielectric permittivity of PVDF-C 3 N 4 composite after 60 °C is likely to be caused by PVDF's softening because at softening temperature, its molecules start to move significantly throughout the crystal region, resulting in relaxations in nanocomposites [46]. Also, the sudden rise in the tangent loss for PVDF-C 3 N 4 at 60 °C results from relaxation processes induced by defects in the PVDF matrix [42].…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…The sudden increase in the dielectric permittivity of PVDF-C 3 N 4 composite after 60 °C is likely to be caused by PVDF's softening because at softening temperature, its molecules start to move significantly throughout the crystal region, resulting in relaxations in nanocomposites [46]. Also, the sudden rise in the tangent loss for PVDF-C 3 N 4 at 60 °C results from relaxation processes induced by defects in the PVDF matrix [42].…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…For instance, several researchers reported high permittivity and low loss values for BST/PVDF functional composite materials upon modifying the surface of BST and adjusting its content in the polymer matrix [28][29][30][31]. Furthermore, the dielectric tunability of these composites was found to be highly influenced by the ceramic volume fraction, the tunability of ceramic phase, shape factor, the phenomenological coefficient ratio of ceramic and polymer (β1 = β2), and the permittivity ratio of ceramic and polymer [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is urgent to design and develop new types of PIs with low permittivity. In order to obtain the low-permittivity polymer materials, two effective strategies are generally considered— (1) reducing the molar polarization rate of the material; (2) introducing air into the polymer matrix ( ε air ≈ 1.0) [ 7 , 8 , 9 , 10 , 11 , 12 ]. For example, Zhang et al reported that a kind of PI fabricated by fluorinated polybenzoxazole derived from the benzoxazine monomer possessed the combined excellent properties of facile synthesis, easy processability, and low permittivity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%